Order and Chaos. Margins of “normality” between diagnosis and therapy: from the preliminary meeting to the plot of a speech to come - Paolo Nardi (Mediterranean Journal of Clinical Psychology, 2015)
As human beings, we are driven by two eternal feelings in perpetual fight: the search for order and the fascination of chaos. Man live inside this fight: between body and language, substance and history, soul and its biological reflections.